2022
DOI: 10.46234/ccdcw2022.009
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Inactivated COVID-19 Vaccines Against Symptomatic, Pneumonia, and Severe Disease Caused by the Delta Variant: Real World Study and Evidence — China, 2021

Abstract: What is already known about this topic?Effectiveness of China's 2 inactivated vaccines (BBIBP-CorV and CoronaVac) against pre-Delta severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) variants ranged from 47% to over 90%, depending on the clinical endpoint, and with greater effectiveness against more severe coronavirus disease 2019 . During an outbreak in Guangdong, inactivated vaccine effectiveness (VE) against the Delta variant was 70% for symptomatic infection and 100% for severe COVID-19. However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
51
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(56 citation statements)
references
References 6 publications
2
51
3
Order By: Relevance
“…Finally, 57 articles were included in the present systematic review [ 6 , 7 , 20 23 , 34 – 84 ]. There were different study designs for included studies, 11 RCTs (161,388 participants) [ 20 , 22 , 23 , 34 41 ], 20 cohort studies (52,782,321 participants) [ 6 , 7 , 42 59 ], and 26 case-control studies (2,584,732 cases) [ 21 , 60 – 84 ]. In total, 11 COVID-19 vaccines (mRNA-1273, BNT162b2, ChAdOx1, Ad26.COV2.S, NVX-CoV2373, BBV152, CoronaVac, BBIBP-CorV, SCB-2019, CVnCoV, and HB02) and 5 VOC (Alpha, Beta, Gamma, Delta, and Omicron) were included in this study.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, 57 articles were included in the present systematic review [ 6 , 7 , 20 23 , 34 – 84 ]. There were different study designs for included studies, 11 RCTs (161,388 participants) [ 20 , 22 , 23 , 34 41 ], 20 cohort studies (52,782,321 participants) [ 6 , 7 , 42 59 ], and 26 case-control studies (2,584,732 cases) [ 21 , 60 – 84 ]. In total, 11 COVID-19 vaccines (mRNA-1273, BNT162b2, ChAdOx1, Ad26.COV2.S, NVX-CoV2373, BBV152, CoronaVac, BBIBP-CorV, SCB-2019, CVnCoV, and HB02) and 5 VOC (Alpha, Beta, Gamma, Delta, and Omicron) were included in this study.…”
Section: Resultsmentioning
confidence: 99%
“…A cohort study in the UAE [14] with 176,640 individuals aged ≥ 15 years showed that two-dose BBIBP-CorV VE was 92.2% for preventing COVID-19-related critical care admission when compared to a non-vaccinated group – a study design and finding similar to ours. Wu [22] and Kang [23] performed real-world studies on the effectiveness of inactivated vaccines used in China against illness caused by the Delta variant in outbreaks in Henan and Guangdong provinces, respectively. Wu and colleagues found that among adults ≥ 18 years, two-dose inactivated VE against severe or critical COVID-19 was 92% [22] , and Kang and colleagues found that two-dose inactivated VE was 100% [23] against severe illness.…”
Section: Discussionmentioning
confidence: 99%
“…Wu [22] and Kang [23] performed real-world studies on the effectiveness of inactivated vaccines used in China against illness caused by the Delta variant in outbreaks in Henan and Guangdong provinces, respectively. Wu and colleagues found that among adults ≥ 18 years, two-dose inactivated VE against severe or critical COVID-19 was 92% [22] , and Kang and colleagues found that two-dose inactivated VE was 100% [23] against severe illness. The two studies were too small to estimate VE separately for BBIBP-CorV and CoronaVac, the two inactivated vaccines in use in the outbreak settings.…”
Section: Discussionmentioning
confidence: 99%
“…In our model, VE in preventing ICU admissions and deaths caused by a Delta variant infection was set at 83.6%, based on real-world VE studies in China and Brazil ( Table 1 ) [ 5 , 20 ]. Should the VE against the infection of the Delta variant be increased to >88% from 51.8% used in the baseline [ 17 ], the “adults + adolescents + children” vaccination strategy is estimated to reduce the number of deaths by 97.9% even in the absence of any NPIs, leading to <74,900 deaths over six months, similar to the annual excess respiratory disease deaths associated with influenza in China [ 45 ] (Figure S9).…”
Section: Resultsmentioning
confidence: 99%
“…Although the inactivated vaccines in use in China as of March 2022 show a relatively low effectiveness against mild and moderate disease caused by Delta variant infection [ 17 , 18 , 20 ], they appear to be highly effective against severe outcomes [ 5 , 18–20 ]. In the context of a constantly changing virus and the evolving epidemiology of the pandemic, it is of great importance to continue to ramp up efforts to increase vaccination coverage by using currently available vaccines.…”
Section: Discussionmentioning
confidence: 99%